Palladium‐Catalyzed Asymmetric Hydrosulfonylation of 1,3‐Dienes with Sulfonyl Hydrazides - Li, Ming‐Ming; Cheng, Lei; Xiao, Li‐Jun; Xie, Jian‐Hua; Zhou, Qi‐Lin (Angewandte Chemie International Edition, 2021)
A highly enantio‐ and regioselective hydrosulfonylation of 1,3‐dienes with sulfonyl hydrazides has been realized by using a palladium catalyst containing a monodentate chiral spiro phosphoramidite ligand. The reaction provided an efficient approach to synthetically useful chiral allylic sulfones. Mechanistic studies suggest that the reaction proceeds through the formation of an allyl hydrazine intermediate and subsequent rearrangement to the chiral allylic sulfone product. The transformation of the allyl hydrazine intermediate to the product is the enantioselectivity‐determining step. A highly enantio‐ and regioselective hydrosulfonylation of 1,3‐dienes with sulfonyl hydrazides by using a palladium catalyst containing a monodentate chiral spiro phosphoramidite ligand is reported. The reaction provides a new strategy for the synthesis of chiral allylic sulfones in high enantioselectivity.